Scouting Extracurricular Program in Character Building for Students at Junior High School 18 Padang - Asril, Zainal; Mulya, Rafil; Rahman, Abdul; Az-zahra, Dwi Wahyuni (Khalaqa: Journal of Education and Learning, 2025)
This research is motivated by initial observations at Junior High School 18 Padang, which has implemented a Scouting extracurricular program as an effort to develop student character. The purpose of this study was to determine the forms of Scouting activities that contribute to character formation, as well as to identify supporting and inhibiting factors in the implementation of the program. This study used a qualitative descriptive approach with field research. Primary data sources included the Vice Principal for Student Affairs, Scout Leaders, and students participating in the extracurricular activities, while secondary data were obtained from the Principal. Data collection techniques were carried out through observation, interviews, and documentation studies, with data analysis through the stages of reduction, presentation, and drawing conclusions. The results showed that the forms of Scouting activities at Junior High School 18 Padang include camping, hiking, pioneering, and community service, each of which plays a role in forming character values ​​such as independence, cooperation, and social care. Supporting factors for the program include government support, the active role of the school, competent leaders, and high student participation. Inhibiting factors include limited transportation, difficulty in obtaining permission from parents, academic schedule conflicts, and minimal supporting facilities. This study recommends the need for synergy between schools, parents, and the government to optimize the implementation of the Scout program as a means of developing student character